FREQUENCY OF PORT SITE INFECTION IN PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY - FARIS, S; SAFI, MH (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic cholecystectomy is a common surgical procedure for the treatment of gallstones. Although considered minimally invasive, port site infections (PSI) remain a concern, potentially impacting patient outcomes and recovery times. Understanding the frequency and risk factors associated with PSI is essential for improving surgical practices and patient safety. Objective: To assess the frequency of port site infection in patients undergoing laparoscopic cholecystectomy. Methods: A cross-sectional study was conducted in the surgery department from January 2, 2024, to April 2, 2024. The study enrolled 120 patients presenting for laparoscopic cholecystectomy. The mean age of the patients was 34.30 ± 9.57 years, and the mean BMI was 25.32 ± 2.21 kg/m². The frequency of PSI was determined, and its association with BMI was analysed using statistical methods, with a significance level set at P < 0.05. Results: The PSI frequency was 6.7% (8 out of 120 patients). There was a notable association between increasing BMI and the occurrence of PSI (P = 0.005). Conclusion: The frequency of PSI in patients undergoing laparoscopic cholecystectomy in this study was 6.7%, suggesting that the procedure is relatively safe for gallbladder removal. Higher BMI was significantly associated with an increased risk of PSI, indicating the need for targeted strategies to mitigate this risk in patients with elevated BMI.